Report on National Seminar on Language Education - Mishra , Mahendra Kumar; Shukla, Neelam (Voices of Teachers and Teacher Educators, 2015)
This report provides an overview of the National Seminar on Language Education, which aimed to address current challenges, trends, and innovative practices in the field of language teaching and learning. Key topics included language acquisition theories, the integration of technology in language instruction, multilingualism, language policy, and the importance of cultural context in language learning. The seminar featured keynote addresses from prominent experts, as well as interactive workshops and panel discussions on the implementation of new pedagogical strategies, such as task-based language teaching, content and language integrated learning (CLIL), and the use of digital tools like language apps and online platforms. The event also provided a platform for sharing best practices and success stories from various educational institutions. The report concludes by summarizing the key insights and recommendations for improving language education at the national level, emphasizing the need for a holistic approach that incorporates both traditional and modern methodologies to cater to diverse learner needs.